Insuring the uninsurable: brokers and incomplete insurance contracts - Neil A. Doherty; Alexander Muermann (Goethe University Frankfurt, Center for Financial Studies (CFS), 2005)
How do markets spread risk when events are unknown or unknowable and where not anticipated in an insurance contract? While the policyholder can 'hold up' the insurer for extra contractual payments, the continuing gains from trade on a single contract are often too small to yield useful coverage. By acting as a repository of the reputations of the parties, we show the brokers provide a coordinating mechanism to leverage the collective hold up power of policyholders. This extends both the degree of implicit and explicit coverage. The role is reflected in the terms of broker engagement, specifically in the ownership by the broker of the renewal rights. Finally, we argue that brokers can be motivated to play this role when they receive commissions that are contingent on insurer profits. This last feature questions a recent, well publicized, attack on broker compensation by New York attorney general, Elliot Spitzer.
urn:nbn:de:hebis:30-23368
Keywords: G22; G24; L14; 330; Incomplete Insurance Contracts; Brokerage; Contingent Commissions; Reputation